Chikungunya in a pediatric cohort: Asymptomatic infection, seroconversion, and chronicity rates. - Blenda de Jesus Pereira; Michelle Queiroz Aguiar Brasil; Jessica de Jesus Silva; Juqueline Rocha Cristal; Isabele de Pádua Carvalho; Maria Carolina Prado Miranda; Daniela Paixão; Ricardo Khouri; Thiago Cerqueira-Silva; Fernanda Castro Boulos; Manoel Barral-Netto; Esper Georges Kalas; et al. (PLoS Neglected Tropical Diseases)
Chikungunya disease, caused by the chikungunya virus (CHIKV), is an acute febrile syndrome that frequently leads to chronic musculoskeletal manifestations. Little is known about the incidence, asymptomatic rate, seroconversion and chronicity after acute CHIKV infection in children and adolescents. We leveraged a nested cohort study within a phase III clinical trial of the Dengue vaccine by the Butantan Institute (DEN-03-IB), in Simões Filho (Bahia-Brazil) to characterize the dynamics of CHIKV infection in the pediatric population. 348 volunteers were included between 2018-2020 and followed for up to three years. Arbovirus surveillance was conducted during medical visits using 1) routine study visits with periodic blood collection; 2) visits due to adverse events (any symptom or illness); and 3) visits due to febrile episodes, with routine blood samples tested for chikungunya, Dengue, and Zika by viral RNA detection using RT-PCR. For cases with suspected arbovirus infection, symptoms and signs were collected with a structured questionnaire. At baseline, 7% (23/348) were positive for antichikungunya IgG. Among 311 that completed follow up (41 months, IQR 38-43), 17% tested positive for CHIKV, with 25 cases positive by RT-PCR and 28 cases by serology. 9.4% were asymptomatic and 3 (12%) developed chronic arthralgia. By the end of the study, only onefifth have been exposed to CHIKV despite several local outbreaks. Seroconversion rate among RT-PCR positive cases was 84%. Chronic arthralgia, though infrequent, was observed in the pediatric population. Our study demonstrates that, within the pediatric population, most CHIKV infections are symptomatic. We observed a small but significant frequency of negative antibody responses following acute infection and instances of chronic disease. These findings underscore the necessity for continuous surveillance and tailored interventions to tackle the unique challenges chikungunya presents in children and adolescents.